THE ISLAMIC SENSE ON LITERARY CRITICISM: A BRIEF HISTORICAL PERSPECTIVE - Moh. Fathoni (P3M STAIN Kudus, 2015)
New Historicism and cultural history have opened up the new approaches to writing histories. However, the last decade national and transnational literary histories have continued to take different approaches, by typical new national literary histories have distinguished the teleology of grand narratives by revised the linear ways into specific subjects and certain conception. In the following discussion, I shall describe how ‘new’ perspective of moral and ideological on history of literary criticism reacted to the crisis of history writing, by appearing the writing of the history of Islamic literary criticism—especially to perceiving the historical writing proposed by M.A.R. Habib, A History of Literary Criticism (2005).